2014
DOI: 10.1093/nar/gku998
|View full text |Cite
|
Sign up to set email alerts
|

Organelle-mimicking liposome dissociates G-quadruplexes and facilitates transcription

Abstract: Important biological reactions involving nucleic acids occur near the surface of membranes such as the nuclear membrane (NM) and rough endoplasmic reticulum (ER); however, the interactions between biomembranes and nucleic acids are poorly understood. We report here that transcription was facilitated in solution with liposomes, which mimic a biomembrane surface, relative to the reaction in a homogeneous aqueous solution when the template was able to form a G-quadruplex. The G-quadruplex is known to be an inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…For mimicking abovementioned cellular (multi)compartments (e.g., artificial organelles [ 2–5 ] and protocells), [ 6–8 ] different synthetic vesicles (e.g., liposomes, [ 9–11 ] hollow capsules, [ 12–14 ] polymersomes [ 15–18 ] and proteinosomes [ 5,6,19,20–22 ] ) and their multicompartments [ 23–26 ] have been designed. Increasing the complexity and diversity of compartments is a crucial issue for mimicking iterative and/or feedback‐controlled processes of and between cellular compartments, [ 27–29 ] for mimicking dynamic self‐assembly and disassembly within protocells, [ 7,20 ] and for mimicking fusion of cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mimicking abovementioned cellular (multi)compartments (e.g., artificial organelles [ 2–5 ] and protocells), [ 6–8 ] different synthetic vesicles (e.g., liposomes, [ 9–11 ] hollow capsules, [ 12–14 ] polymersomes [ 15–18 ] and proteinosomes [ 5,6,19,20–22 ] ) and their multicompartments [ 23–26 ] have been designed. Increasing the complexity and diversity of compartments is a crucial issue for mimicking iterative and/or feedback‐controlled processes of and between cellular compartments, [ 27–29 ] for mimicking dynamic self‐assembly and disassembly within protocells, [ 7,20 ] and for mimicking fusion of cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…The biological membranes of cells and organelles play a key role in living organisms by providing spatially isolated environment for enzymatic reactions and transmembrane transport for the communication between different compartments. [1] For mimicking abovementioned cellular (multi)compartments (e.g., artificial organelles [2][3][4][5] and protocells), [6][7][8] different synthetic vesicles (e.g., liposomes, [9][10][11] hollow capsules, [12][13][14] polymersomes [15][16][17][18] and proteinosomes [5,6,19,[20][21][22] ) and their multicompartments [23][24][25][26] have been designed. Increasing the complexity and diversity of compartments is a crucial issue for mimicking iterative and/or feedbackcontrolled processes of and between cellular compartments, [27][28][29] for mimicking dynamic self-assembly and disassembly within protocells, [7,20] and for mimicking fusion of cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…DPPC liposome was prepared followed by a procedure reported earlier [63] . Briefly, appropriate amount of DPPC was dissolved in 2 : 1 molar ratio chloroform methanol solvent mixture.…”
Section: Methodsmentioning
confidence: 99%
“…DPPC liposome was prepared followed by a procedure reported earlier. [63] Briefly, appropriate amount of DPPC was dissolved in 2 : 1 molar ratio chloroform methanol solvent mixture. Next, solvent was evaporated followed by overnight incubation under vacuum to produce thin film.…”
Section: Preparation Of Liposomementioning
confidence: 99%
“…It has been found that a combination of electrostatic attraction and the size compatibility of the hydrated monovalent or divalent cations govern the selective binding of these cations to the DNA duplex [7,8]. On the other hand, small molecular ions such as tetramethyl ammonium (TMA + ) and 2hydroxy-N,N,N-trimethylethanaminium (CHO + ) bind to the specific regions of DNA duplex, triplex and quadruplex by forming additional hydrogen bonds between molecular ion sites and electronegative DNA base atoms and other non-covalent interactions [9,10] contribute as well. DNA duplexes may also undergo rapid structural transitions in response to certain external stimuli, such as pH [11] of the solution, electrical signals [12] and macromolecular assemblies [13].…”
Section: Introductionmentioning
confidence: 99%